Rullierinereis imajimai nom. nov., a replacement name for R. profunda Imajima, 2009, secondary homonym to R. profunda (Hartman, 1965), formerly Namalycastis profundus - Tanaka, Masaatsu; Sato, Masanori (Zootaxa, 2017)
Hartman (1965) described a nereidid species, Namalycastis profundus[sic], based on a deep-sea specimen collected from off Bermuda (1000 m deep) in the NW Atlantic. Although Hartman (1965) did not mention its etymology, the specific name is believed to be derived from the Latin adjective “profund-” meaning “deep.” Because Namalycastis is feminine in gender (Glasby et al. 2016), the original specific name as masculine was incorrect and must be corrected to N. profunda for mandatory gender agreement under Articles 31.2 and 34.2 of the International Code of Zoological Nomenclature (hereafter, “the Code”) (International Commission of Zoological Nomenclature 1999).